From Ganga to Pahalgam: India’s Arc of Strategic Deceit - Asifa Tanveer (Policy Perspectives, 2025)
India, given its geographic size, population, economic aspirations, and claims about democratic and secular values, has consistently positioned itself as a regional hegemon. This image is reinforced through assertive regional policies and global diplomatic posturing. However, its recurring tendency to attribute blame to Pakistan for its domestic instabilities, particularly ‘terrorist’ events, often without any corroborating evidence, raises doubts whether this is a calculated strategic policy or a reactive event-based posture. Multiple analyses of the incidents that India blamed Pakistan for, suggest that they were instrumentalized to implicate Pakistan thereby serving broader political and strategic objectives. This paper explores the history and use of such false flag acts designed to implicate Pakistan to contextualize India’s tendency of attributing blame to the former. It examines whether Pahalgam incident of April 22, 2025, and India’s response to it, reflect genuine security concerns, or a broader political or diplomatic agenda. It draws on case studies, media analyses, and international responses, to evaluate the implications of this and other such events for regional and global stability. It also explores how such incidents help India deflect scrutiny over human rights abuses in the IIOJ&K and the denial of civil liberties to minorities, revealing a method in its madness.